Competitive Relationship Between Cleistocalyx operculatus and Syzygium jambos Under Well-Watered Conditions Transforms Into a Mutualistic Relationship Under Waterlogging Stress - Yang, Fan; Zhang, Juan; Cisse, El-Hadji Malick; Li, Da-Dong; Guo, Lu-Yao; Xiang, Li-Shan; Miao, Ling-Feng (Frontiers in Plant Science, 2022)
Competition and abiotic stress (WL) represent main factors limiting plant growth and determining plant resistance and distribution patterns in wetland ecosystems. Plant survival and adaptation are considered criteria of principal priority for the screening of plant species for wetland ecosystem restoration. WL influence plant species in wetlands via the deterioration of the plant root environment which lead to oxygen deficiency that affect plant growth, photosynthesis, respiration, and other metabolic processes. A suitable plant species was determined according to tolerance to WL during wetland vegetation recovery activities. Thus, two tree species (Cleistocalyx operculatus and Syzygium jambos) that showed a certain waterlogging tolerance were chosen to study their behaviors in different planting model and environmental conditions. Given that interspecific relationship should be considered during plant community construction, the eco-physiological adaptable mechanisms between these woody plants under well-watered condition and waterlogging stress were explored. Results showed that both species were waterlogging-tolerant species due to their ability to adapt to submergence conditions for 120 days. Moreover, C. operculatus possessed stronger tolerance to waterlogging stress because of a significant adventitious roots biomass accumulation. A competitive relationship was found between C. operculatus and S. jambos under well-watered condition, and C. operculatus showed better growth performance benefited from morphological responses (plant height, number of blade and leaf area) and endogenous hormone variations. In comparison, S. jambos suffered some negative effects when the well-watered mixed planting was used. However, the competitive relationship under well-watered condition was transformed into mutualistic relationship under waterlogging stress. The mixed planting under waterlogging condition significantly improved the tolerance of C. operculatus and S. jambos to waterlogging stress, compared with the monoculture., Especially, S. jambos showed improvements in root length, root surface area, and redox equilibration between lower levels of relative conductivity, malondialdehyde, and O2•− and had increased levels of non-enzymatic antioxidant components, such as reduced glutathione and soluble proteins. The interspecific relationship between C. operculatus and S. jambos was altered by waterlogging stress, and both showed improved tolerance to waterlogging stress. This study can provide shed light on suitable plant species selection and plant community construction during the revegetation activities in wetland zones.